Soil resistivity measurements in UPM Serdang campus for grounding system purposes - Wan Ahmad, Wan Fatinhamamah; Palahuddin, Syahrul Hilmi; Osman, Miszaina (Institute of Electrical and Electronics Engineers, 2024)
Grounding systems is a fundamental part in an electrical power engineering system. It is important for ensuring the safety of occupants, to protect electrical equipment from damage, minimize the risk of electrical hazards and maintain a stable system during both normal and fault conditions. Hence, a grounding system must provide a path for fault currents to safely dissipate into Earth while preventing electrical shock hazard, and reduce and limit the damage to any electrical equipment connected to it. However, traditional grounding systems may not always be able to provide the required level of conductivity, especially in high soil resistivity sites or in applications where high fault currents are anticipated. Resistivity of the surrounding soil is one of the parameters that can be easily manipulated for an efficient grounding system to be made available as it is influenced by factors such as geographical location, moisture content, temperature, and soil composition. In regions with poor natural soil conductivity or environments characterized by seasonal fluctuations in resistivity, the deployment of natural enhancement material is merged as a critical solution. In this work, three sites located around Universiti Putra Malaysia Serdang Campus, Selangor, MALAYSIA were tested for its soil resistivity. This is meant for grounding system installations with new natural enhancement material mixtures in the vicinity of vertical ground conductors. Site 2 with high resistivity and most homogeneous soil would be chosen to test the grounding system installations, while Site 1 with the lowest soil resistivity would be installed with Reference grounding system as comparison purposes. Note that a Reference grounding system is installed without any natural enhancement material mixture in the vicinity of the vertical ground conductor.